Biological effects of intraoperative radiation therapy: histopathological changes and immunomodulation in breast cancer patients - Orozco, Javier I. J.; Valdez, Betsy J.; Matsuba, Chikako; Simanonok, Michael P.; Ensenyat-Mendez, Miquel; Ramiscal, Judi Anne B.; Salomon, Matthew P.; Takasumi, Yuki; Grumley, Janie G. (Frontiers in Immunology, 2024)
Introduction: Intraoperative radiation therapy (IORT) delivers a single accelerated radiation dose to the breast tumor bed during breast-conserving surgery (BCS). The synergistic biologic effects of simultaneous surgery and radiation remain unclear. This study explores the cellular and molecular changes induced by IORT in the tumor microenvironment and its impact on the immune response modulation. Methods: Patients with hormone receptor (HR)-positive/HER2-negative, ductal carcinoma in situ (DCIS), or early-stage invasive breast carcinoma undergoing BCS with margin re-excision were included. Histopathological evaluation and RNA-sequencing in the re-excision tissue were compared between patients with IORT (n=11) vs. non-IORT (n=11). Results: Squamous metaplasia with atypia was exclusively identified in IORT specimens (63.6%, p=0.004), mimicking DCIS. We then identified 1,662 differentially expressed genes (875 upregulated and 787 downregulated) between IORT and non-IORT samples. Gene ontology analyses showed that IORT was associated with the enrichment of several immune response pathways, such as inflammatory response, granulocyte activation, and T-cell activation (p<0.001). When only considering normal tissue from both cohorts, IORT was associated with intrinsic apoptotic signaling, response to gamma radiation, and positive regulation of programmed cell death (p<0.001). Using the xCell algorithm, we inferred a higher abundance of gd T-cells, dendritic cells, and monocytes in the IORT samples. Conclusions: IORT induces histological changes, including squamous metaplasia with atypia, and elicits molecular alterations associated with immune response and intrinsic apoptotic pathways. The increased abundance of immune-related components in breast tissue exposed to IORT suggests a potential shift towards active immunogenicity, particularly immunedesert tumors like HR-positive/HER2-negative breast cancer.